ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN AYAM POTONG UNTUK KONSUMSI RUMAH TANGGA DI KECAMATAN SAKO - Festriani Christine; Syamsurijal AK; Suhel Suhel (Jurnal Ekonomi Pembangunan, 2003)
The purpose of this research is to analyze a few factors that influence the demand for breeder chicken in Sako Palembang. Income level, family number, the price of breeder chicken and price of fish are the independent variable and demand of breeder chicken as the dependent variable. Quantitative for analysis are with regression models. The result on regression model has improved that the independent variable significantly influencing the dependent variable. Keywords: Demand for breeder chicken, income level, family number, the price of breeder chicken, and price of fish.